2020
DOI: 10.1101/2020.04.30.068338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piezo1 activation attenuates thrombin-induced blebbing in breast cancer cells

Abstract: Cancer cells exploit a variety of migration modes to leave primary tumors and establish metastases, including amoeboid cell migration facilitated by bleb formation. Here we demonstrate that thrombin induces dynamic blebbing in the MDA-MB-231 breast cancer cell line, and confirm that PAR2 activation is sufficient to induce this effect. Cell confinement has been implicated as a driving force in bleb-based migration. Unexpectedly, we find that gentle contact compression, exerted using a "Cell Press" to mechanical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Piezo1 downregulation can accelerate cell migration in lung cancer by promoting ameboid-type migration [ 61 , 62 ]. In MDA-MB-231 cells, Piezo1 inhibited blebbing, providing more evidence that Piezo1 prevents ameboid migration [ 64 ]. In studies of non-small cell lung cancer (NSCLC), Piezo1 knockdown enhanced migration and tumor growth [ 63 ].…”
Section: Invasion and Migrationmentioning
confidence: 99%
“…Piezo1 downregulation can accelerate cell migration in lung cancer by promoting ameboid-type migration [ 61 , 62 ]. In MDA-MB-231 cells, Piezo1 inhibited blebbing, providing more evidence that Piezo1 prevents ameboid migration [ 64 ]. In studies of non-small cell lung cancer (NSCLC), Piezo1 knockdown enhanced migration and tumor growth [ 63 ].…”
Section: Invasion and Migrationmentioning
confidence: 99%
“…For example, Piezo1 activation inhibited blebbing of MDA-MB-231 breast cancer, reducing its ameboid migration. 48 Conversely, blockage of Piezo1 using GsMTx-4 reduced migration velocity and motility of MCF-7 breast cancer cells, suggesting that Piezo1 promoted cancer migration and invasion. 49 Due to the unavoidable diffusion in devices in our study, Yoda1 may directly affect cancer and endothelial cell activities; hence follow-up studies are needed.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, it has been shown that the tumor microvasculature is under a "pathological state of coagulation." In fact, the introduction of thrombin, which activates PAR-1 signaling, was recently shown to promote blebbing in breast cancer cells (O'Callaghan et al 2020). Thus, in terms of how they may regulate the motile behavior of melanoma cells, several aspects of 3D confinement within microchannels remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although here we have simulated channel-like environments in general, it remains possible that the introduction of channel coatings, such as VCAM-1 (which decorates micro-vessel walls), may also regulate the motile behavior of melanoma cells. Additionally, it has been shown that the tumor micro-vasculature is under a “pathological state of coagulation.” In fact, the introduction of thrombin, which activates PAR-1 signaling, was recently shown to promote blebbing in breast cancer cells 20 . Thus, in terms of how they may regulate the motile behavior of melanoma cells, several aspects of 3D confinement within microchannels remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%